Developing a Method to Precisely Locate the Keypoint During Craniotomy Using the Retrosigmoid Keyhole Approach: Surgical Anatomy and Technical Nuances - Jian, Zhi-heng; Sheng, Min-feng; Li, Jia-yan; An, De-zhu; Weng, Zhi-jian; Chen, Gang (Frontiers in Surgery, 2021)
Objective: To explore the precise location of the keypoint in the craniotomy of retrosigmoid keyhole approach. Methods: 20 dry skulls and 10 wet cadaveric specimens were used in the study. On the inner surface of dry skulls, the point of the inferior margin of the transverse sinus–posterior margin of the sigmoid sinus junction (TSJ) was marked, and the corresponding point on the external surface of temperal mastoid process was identified as the keypoint (D). The length (AD) between the keypoint and the top point of the digastric groove (A), the length (BD) between the keypoint and the mastoidale (B), and the length (CD) between the keypoint and asterion (C) were noted. Based on the relationship among the anatomical landmarks of dry skulls, an accurate method for locating the keypoint was developed. Then, the method was imitated in wet cadaveric specimens to verify our observations. Accuracy,safety, rapidity and minimal invasion were evaluated. Results:1.In the dry skulls, the value of AD, BD, CD averaged 16.98 ± 3.58 mm, 34.48 ± 3.77 mm, 18.49 ± 3.65 mm on the left and 15.37 ± 3.25 mm, 33.57 ± 3.30 mm, 20.89 ± 4.89 mm on the right respectively. There was no statistically significant difference between the left and right sides (P>0.05). We oriented the drilling point:12mm above the top point of the digastric groove on a straight line perpendicular to the base line according to Frankfort horizontal plane(FHP) and throuth the top point of the digastric groove. 2. The retrosigmoid keyhole approach was imitated in 10 wet cadaveric specimens with our method of the research. Operative area was exposed clearly in all wet cadaveric specimens. No venous sinus rupture occurred. The average craniotomic time was 28.74±3.89 minutes. Conclusions: this method could ensure a safe, accurate, and rapid craniotomy while preserving the visibility of the operating field and preventing injury to the venous sinuses.